COMMUNITY DIAGNOSIS PERMASALAHAN KESEHATAN DI NYUTRAN RT 64 RW 20, KELURAHAN WIROGUNAN, KOTA YOGYAKARTA - Utami, Putri Retno; Matahari, Ratu (APMa Jurnal Pengabdian Masyarakat, 2022)
In 2021 there were 3956 cases of hypertension from 11218 people in Wirogunan Sub-district. The prevalence rate of hypertension in Wirogunan Sub-district reached 35.26%. This Field Learning Experience activity aims to provide education to the public on how to avoid the hypertension. The technique used in this activity to obtain data is the In-Depth Interview which is the technique through door-to-door interviews using questionnaires, while the data analysis method used is descriptive statistical analysis method, which is to present statistical data to describe the state of disease and health distribution in Nyutran Village. This activity was carried out in Nyutran Village, Wirogunan Sub-district, Yogyakarta City. The results of community diagnosis from 30 samples (Family Cards) in Nyutran Village showed cases of non-communicable diseases, namely hypertension as a priority health problem as many as 14 cases (46%), while the most cases of communicable diseases were diarrheal diseases as many as 12 cases (40%). The results of the Occupational Safety and Health (K3) assessment showed that there were 21 samples (70%) who did not use heavy objects moving aids, 11 samples (37%) did not use LPG safety, 14 samples (46%) used dug wells. USG method for hypertension obtained an Urgency value of 4 (Urgent / Large), Seriousness of 5 (Very Serious / Very Large) and Growth of 4 (Fast / Large). Solutions or Interventions in this Field Learning Experience activity were chosen with counseling activities about Hypertension using posters and pamphlets as intervention media. This intervention activity was carried out on July 7, 2022 in one of the residents' houses through a meeting of mothers for family welfare development.